Molecular evolution of bumble bee vitellogenin and vitellogenin‐like genes. Issue 13 (5th June 2021) - Zhao, Fang; Morandin, Claire; Jiang, Kai; Su, Tianjuan; He, Bo; Lin, Gonghua; Huang, Zuhao
Abstract: Vitellogenin (Vg), a storage protein, has been significantly studied for its egg yolk precursor role in oviparous animals. Recent studies found that vitellogenin and its Vg‐like homologs were fundamentally involved in many other biological processes in social insects such as female caste differences and oxidative stress resilience. In this study, we conducted the first large‐scale molecular evolutionary analyses of vitellogenin coding genes ( Vg ) and Vg‐like genes of bumble bees, a primitively eusocial insect belonging to the genus Bombus. We obtained sequences for each of the four genes ( Vg, Vg‐like‐A, Vg‐like‐B, and Vg‐like‐C ) from 27 bumble bee genomes (nine were newly sequenced in this study), and sequences from the two closest clades of Bombus, including five Apis species and five Tetragonula species . Our molecular evolutionary analyses show that in bumble bee, the conventional Vg experienced strong positive selection, while the Vg‐like genes showed overall relaxation of purifying selection. In Apis and Tetragonula; however, all four genes were found under purifying selection. Furthermore, the conventional Vg showed signs of strong positive selection in most subgenera in Bombus, apart from the obligate parasitic subgenus Psithyrus which has no caste differentiation. Together, these results indicate that the conventional Vg, a key pleiotropic gene in social insects, is the most rapidly evolving copy, potentially due to its multiple known social functions for both worker and queen castes. This study shows that concerted evolution and purifying selection shaped the evolution of the Vg gene family following their ancient gene duplication and may be the leading forces behind the evolution of new potential protein function enabling functional social pleiotropy. Abstract : In this study, we conducted the first large‐scale molecular evolutionary analyses of vitellogenin‐coding genes ( Vg ) and Vg ‐like genes (Vg‐like‐A, Vg‐like‐B, and Vg‐like‐C) of bumble bees, a primitively eusocial insects belonging to the genus Bombus. The overall dN/dS ratio of the conventional Vg was 1.311, and this gene was under strong positive selection in most (9/10) subgenera in Bombus, apart from the obligate parasitic subgenus Psithyrus (dN/dS = 0.713) which has no caste differentiation.